P185 Urine biomarker profiles associated with copd exacerbations. (15th November 2017) - Yousuf, A; Parekh, G; Watson, L; George, L; Singapuri, A; Mistry, V; Davis, P; Brightling, C
Abstract : Introduction: COPD exacerbations cause considerable morbidity and mortality. Early identification and appropriate treatment might improve patient outcomes. We sought to determine whether urinary biomarkers are associated with a COPD exacerbation. Method: Urine samples from paired stable and exacerbation visits from 55 subjects were available from the COPD-BEAT study. 50 biomarkers were analysed in each sample at Mologic (Mologic LTD). Biomarkers that fulfilled the criteria i) a significant parametric pairwise t-test (p≤0.05) and ii) area under the receiver-operator characteristic curve (AUROC ≥0.59) were selected for inclusion in a logistic regression model. Results: The biomarkers that met criteria and were taken forward for further analysis are shown in Table 1 . Of these CC16, CRP, MMP8 and NGAL combined had an AUROC 0.82 (95% confidence interval 0.74 to 0.90). The Youden's index gave a sensitivity and specificity of 78% and 82% respectively. Conclusion: COPD exacerbations can be identified by urinary biomarkers. The biomarker panel requires further validation in a prospective longitudinal study.